Is opera a literary genre? - Pueo, Juan Carlos (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Opera is generally considered a musical genre, but its literary statute seems to be rather uncertain. The aim of this article is to clarify this subject, taking as reference literary genre theory, theatrical theory and musical semiotics. Literary theory must take into consideration the specificity of certain literary genres whose reception is intended to be accompanied by music. Theatrical genres defines themselves by the physical presence of one o more actors that impersonate some characters for an audience, so this genres can be classified by the use or the disuse of language and/or music: this means that opera occupies a place in the classification of literary genres because of its conjunction of language and music. This conjunction is not mere yuxtaposition, it has to be thought as a symbiosis between two semiotic systems that collaborate to produce an specific form of musical-literary work that must be considered a literary and theatrical genre with special characteristics.